Digital Transformation and Innovation Adoption in Maritime Logistics: Technology Integration, IoT Implementation, and Organizational Change Management - Winarno Winarno; Tri Cahyadi; Chanra Purnama; Nathanael Suranta (Global Research Collaboration, 2026)
The maritime logistics sector is undergoing a profound digital transformation driven by emerging technologies such as the Internet of Things, artificial intelligence, and smart infrastructure systems, yet the organizational and strategic dimensions of this transition remain insufficiently understood. This study examines the adoption of digital technologies in maritime logistics by analyzing the interplay among technology integration processes, organizational change management, and strategic innovation frameworks. Employing a qualitative research design that combines thematic analysis, cross-group comparison, and narrative synthesis, the study draws upon expert consultations and document analysis involving maritime technology specialists, logistics management professionals, and academic researchers. The findings reveal three principal themes: the multi-layered architecture of digital technology integration in maritime operations, the critical role of organizational readiness and human capital development in mediating successful adoption, and the necessity of adaptive strategic frameworks that balance innovation ambition with operational continuity. The study contributes a conceptual model linking digital transformation drivers, organizational enablers, and strategic outcomes, offering theoretical insights for innovation management scholarship and practical guidance for maritime organizations navigating the complexities of technology-driven operational change.